Analisis Anggaran Biaya Produksi dalam Menunjang Efektivitas Pengendalian Biaya Produksi untuk Meningkatkan Laba - Tiya Bella Aprillia; Sri Luayyi; Fauziyah Fauziyah (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
It is important for companies to calculate production cost budgets in order to increase a company's profits. Researchers conducted research on CV. GTT Kediri by calculating the production cost budget. The researcher aims to find out how production cost budget analysis supports the effectiveness of controlling production costs to increase profits. In this research, researchers used quantitative descriptive research. The data sources used in this research are interviews and documentation as well as the analysis techniques used, namely calculating the production cost budget, calculating the effectiveness of production costs, calculating the cost of production, and comparing profit and loss report data from the company with research results. The result of this research is that by calculating the production cost budget, it proves that production costs can be said to be effective because the results are above 90%. Calculating the production cost budget is able to increase company profits, the company's net profit data for 2022 is IDR 767,264,000. then the net profit results from the research without using the 2023 production cost budget calculation were IDR 892,934,000 and the profit and loss results from research using the 2023 production cost budget calculation were IDR 901,705,000.